Cobalt nanoparticles mechanically deposited on α‐Al2O3: a competitive catalyst for the production of hydrogen through ethanol steam reforming. Issue 2 (5th October 2018) - Riani, Paola; Garbarino, Gabriella; Canepa, Fabio; Busca, Guido
Abstract: BACKGROUND: Cobalt (Co)‐containing materials are promising catalysts for Ethanol Steam Reforming (ESR) allowing renewable hydrogen production. Usually, complex catalysts are used where Co, produced by impregnation or coprecipitation, is supported on oxide or carbon‐based materials. Here Co nanoparticles (CoNPs) mechanically mixed with α‐Al2 O3 are prepared and tested for ESR. RESULTS: CoNPs mechanically mixed with α‐Al2 O3 are very active catalysts in ESR at 773 K, even when retaining amorphous structure for Co. After annealing at 773 K, CoNPs crystallize into a cubic structure. These materials are even more active in ESR at 773 K with hydrogen yields ≈70% and nearly stable performances after 8 h on‐stream. Hydrogen yield is limited by the formation of some CH4, probably as a result of acetaldehyde formation and successive decomposition. Two kinds of Co particles are found in the used but still active catalysts: the former ones interacting with alumina and embedded in graphitic carbon, that are probably the most active components, whereas the latter are 'isolated' and partly aggregated CoNPs embedded in carbon nanotubes, which are probably less active in ESR. CONCLUSIONS: Mechanical mixing of CoNPs with α‐Al2 O3 produced active and stable catalysts for ESR. The 'chemical' interaction of CoNPs with the support may not be an important factor for ESR catalysts. © 2018 Society of Chemical Industry